Analisis Pelanggaran Etika Profesi Akuntansi (Studi Kasus Pada PT. Great River International Tbk) - Nenny Lamsriani; Yolla Febria; Hamsarida Hamsarida; Monika Kapitan (JOURNAL SAINS STUDENT RESEARCH, 2024)
Audit is a professional service provided by a Public Accounting Firm (KAP) and carried out by auditors as a form of service to provide adequate confidence in the fairness of financial reports. To maintain the trust of clients and other users of financial reports, public accountants must have adequate competence and comply with the principle of compliance with regulations based on existing standards. However, even though there are many laws and standards, there is still the possibility of auditors committing fraud or defrauding the public.